Pelakor Phenomenon in the Digital Era: Analysis of the “Gayung Love Pink” Case and the Dynamics of Infidelity in Personal and Professional Environments - Fitriyah, Qoriatul; Wahyudi, Muhammad Prihadi Eko (Journal of Urban Sociology, 2025)
This research explores the 'pelakor' phenomenon, a term that describes women who have affairs with married men, in terms of Indonesian urban contemporary. This study focused on the downfall of social and relational norms, both in professional and personal space. Qualitative analyses were held between January and March 2025, with social media and news reports, interviews, and study literature. This research exposes the repeated norm-breaking in the school, workplace, and friendship environments. The cases exposed in this study show that individuals are purposely pursuing extramarital affairs due to financial motives and related career advancement. The findings show the deeper trend of exploitation of marriage and women's friendships to pursue affairs through planned emotional manipulations.Keywords: pelakor, extramarital affair,  infidelity, social media, tiktok, urban society, social boundaries